The Implementation and Evaluation of Islamic Values Integration in Local Content Subjects in Bengkulu’s Senior High Schools - HK, Nasron (Journal of Cultural Analysis and Social Change, 2025)
Education plays a crucial role in shaping generations that are not only academically excellent but also characterized by strong moral values rooted in religion and local culture. This study aims to describe the implementation and evaluate the effectiveness of Islamic values integration in local content subjects in Bengkulu’s senior high schools, while also analyzing teachers’ strategies, students’ responses, and the supporting and inhibiting factors of the integration process. The study employed a mixed-methods approach with a sequential explanatory design. The quantitative phase involved administering Likert-scale questionnaires to 137 students and 30 teachers, while the qualitative phase included interviews, classroom observations, and document analysis involving six teachers, six students, and two principals. The findings indicate that teachers (M = 4.706) and students (M = 4.657) hold highly positive perceptions toward the integration of Islamic values in local content, with over 93% of respondents falling into the agree and strongly agree categories. Qualitative data confirm that integration strategies are implemented through brief lectures, practical activities such as the call to prayer and funeral washing, and reflective discussions. Students demonstrated greater enthusiasm for practice-based learning compared to lectures, while document analysis revealed that affective indicators such as responsibility and tolerance had been incorporated into lesson plans. Overall, the study concludes that the integration of Islamic values in local content subjects effectively strengthens students’ character education. Recommendations include enhancing practice-based learning strategies, developing lesson plans with clearer affective indicators, providing training for non-Islamic Education teachers, and formulating official evaluation guidelines for policymakers.